Prey-capture Strategies of Fish-hunting Cone Snails: Behavior, Neurobiology and Evolution - Olivera, Baldomero M. (Brain Behav Evol, 2015)
The venomous fish-hunting cone snails (Conus) comprise eight distinct lineages evolved from ancestors that preyed on worms. In this article we attempt to reconstruct events resulting in this shift in food resource by closely examining patterns of behavior, biochemical agents (toxins) that facilitate prey capture, and the combinations of toxins present in extant species. The first sections introduce three different hunting behaviors associated with piscivory: “taser and tether”, “net engulfment”, and “strike and stalk”. The first two fish-hunting behaviors are clearly associated with distinct groups of venom components, called cabals, which act in concert to modify the behavior of prey in a specific manner. Derived fish-hunting behavior clearly also correlates with physical features of the radular tooth, the device that injects these biochemical components. Mapping behavior, biochemical components, and radular tooth features onto phylogenetic trees shows that fish-hunting behavior emerged at lease twice during evolution. The system presented here may be one of the best examples where diversity in structure, physiology and molecular features was initially driven by particular pathways selected through behavior.